2019
DOI: 10.3390/biom9090465
|View full text |Cite
|
Sign up to set email alerts
|

Anacardium Plants: Chemical,Nutritional Composition and Biotechnological Applications

Abstract: Anacardium plants are native to the American tropical regions, and Anacardium occidentale L. (cashew tree) is the most recognized species of the genus. These species contain rich secondary metabolites in their leaf and shoot powder, fruits and other parts that have shown diverse applications. This review describes the habitat and cultivation of Anacardium species, phytochemical and nutritional composition, and their industrial food applications. Besides, we also discuss the secondary metabolites present in Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 97 publications
4
43
0
4
Order By: Relevance
“…It is a perennial crop belonging to the anacardicaea family and consists of 77 genera and 700 species; of which only 20 of the 700 species are widely distributed in the tropics (Mitra et al, 2007;Tinalu and Barford, 2008;Trox et al, 2010). Cashew tree has a life span of about thirty to forty years in which it takes about three to four years to reach its full production potentials (Salehi et al, 2019). The raw cashew nut (RCN) is the main commercial product of the cashew tree, though yields of the cashew apple are eight to ten times the weight of the raw nuts (Azam-Ali and Judge, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is a perennial crop belonging to the anacardicaea family and consists of 77 genera and 700 species; of which only 20 of the 700 species are widely distributed in the tropics (Mitra et al, 2007;Tinalu and Barford, 2008;Trox et al, 2010). Cashew tree has a life span of about thirty to forty years in which it takes about three to four years to reach its full production potentials (Salehi et al, 2019). The raw cashew nut (RCN) is the main commercial product of the cashew tree, though yields of the cashew apple are eight to ten times the weight of the raw nuts (Azam-Ali and Judge, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The Anacardium genus comprise of about 20 species, which are found mainly in the tropical areas of the New world. Of these species, A. occidentale is the only well-known species which is widely cultivated for its nutritious nuts (Salehi et al 2019). Generally, the cashew exhibits two or more vegetative flushing and one reproductive flushing in an annual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies have been conducted to evaluate the qualitative and quantitative phytochemical constituents of A. occidentale and are summarized in the form of a comprehensive review by [ 48 ]. Different vitamins and functional biofactors were reported in the cashew leaves, e.g., vitamin C, vitamins B2 and B3, thiamine, methyl gallute, leucocyanidin, leucodelphinidin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies revealed the presence of a number of phenolic compounds in the cashew leaves, e.g., 2-hydroxy-6-pentadecylbenzoic acid, hyperoside, amentoflavone derivate, myricetin-O-glycoside, kaempferol-3-O-xyloside, quercetin-3-O-xyloside, quercetin-3-O-arabinofuranoside, quercetin-3-O-arabinopyranoside, quercetin-3-O-rutinoside, etc. [ 48 ]. In another study, fresh cashew leaves were subjected to steam distillation for the evaluation of essential oils and found β -phellandrene + limonene (17.5%), methyl chavicol (11.4%), germacrene B (8%), and trans- α -bergamotene (7.9%) in the dominant quantities [ 49 ].…”
Section: Discussionmentioning
confidence: 99%